P9 Indications and results of systemic to pulmonary shunts – results from a national database. (2nd March 2016) - Dorobantu, DM; Pandey, R; Sharabiani, MT; Mahani, AS; Angelini, GD; Martin, RP; Stoica, SC
Abstract : Objective: The systemic-to-pulmonary shunt (SPS) remains an important palliative therapy in many congenital heart defects. Unlike other surgical treatments, the mortality after shunt operations has risen. We used an audit dataset to investigate potential reasons for this change and to report national results. Patients and methods: A total of 1993 patients classified in 13 diagnoses underwent an SPS procedure between 2000 and 2013. Indication trends by era and also results before repair or next stage are reported. A dynamic hazards model with competing risks and modulated renewal were used to determine predictors of outcomes. Results: Usage of SPS in Tetralogy of Fallot (ToF) has significantly decreased, in the last decade, with cases of single ventricle (SV) and pulmonary atresia (PA) with septal communication increasing (p < 0.001 for trends). This is correlated with an increase of early mortality from 5.1% in the first half of the decade to 9.8% in the latter (p = 0.007 for trend). At 1.5 years, 13.9% of patients have died, 17.8% had a shunt reintervention and 68.3% of patients are alive and reintervention-free. Survival and freedom from reintervention in the main diagnosis groups can be seen in Figures A and B . Low weight, PA-IVS, SV and central shunt type are among the factors associated with increased mortality, while PA-VSD, corrected transposition, isomerism, central shunt and low weight are among those associated with increased reintervention, also having a dynamic effect on the relative risk when compared to ToF patients. Shunt reinterventions are not associated with worse outcomes when adjusted by other covariates, but they do have higher 30-day mortality if occurring earlier than 30 days from the index (p < 0.001). Patients operated in later years were found to have significantly lower survival at distance from index. Conclusions: The observed historical rise in mortality for shunt operations relates to complex factors including changing practice for repair of ToF and for univentricular palliation. PA and SV patients are the groups of patients at the highest risk of death. Small size, shunt type and underlying anatomical defect are the main determinants of outcomes. Trends in indication and mortality seem to point that more severely ill patients benefit from shunting, but with an increase in mortality.